Meningkatkan Kemampuan Pemahaman Literasi Dasar Membaca dan Minat Baca Siswa dengan Metode Adaptasi PRAHTAM-TARL - Supriyanto, Supriyanto (Jurnal Didaktika Pendidikan Dasar, 2024)
Based on PISA’s data, Indonesia’s level of literacy is currently low, especially among elementary students because teachers’ media and method are outdated. This problem is occuring at SDN Bandar Kidul 2. Based on the observation, many students are still unable to read and known the letter. The number of students who visit the school library is low. The government has advised teachers to learn by using a variety of teaching techniques. Therefore, the purpose of this study is to test the efficacy of Pratham-TaRL method in improving reading comprehension and interest among students in 2nd grade at SDN Bandar Kidul 2. The research used a descriptive with qualitative approach. Data collection was conducted through oral tests using initial literacy assessment instruments to determine students’ comprehension. Questionnaires and document data were collected to assess students’ reading interests. The results of the study suggest that implementing this model will increase student’s reading comprehension. The participants have shown promising reading comprehension ranging from reading letters to words 29%, words to paragraphs 11%, and paragraphs to texts 45%. It has influenced the students’ reading interest, by measuring the increasing 37% number of students who visit the school library each week.